PEMBERDAYAAN EKONOMI DIGITAL SEBAGAI SARANA PROMOSI BAGI PELAKU UMKM DUSUN KALANGAN - Haifah Nabilatul Azizah; Qurotul Aini; Nur Kholidah (Institut Agama Islam Syubbanul Wathon Magelang, 2021)
The digital economy has had a positive influence on SMMEs actors. The impact of the development of the digital economy has become a forum for carrying out various kinds of economic transactions during the new normal era. However, there are still limited information and knowledge of the digital economy as a sales medium in the hamlet. Therefore, community service activities are needed in the form of assistance, especially for artisans and MSME actors in order to increase awareness of utilizing the digital economy, the mentoring method used is the PAR (Participatory action research) method. Thus, in the process of community service, the team is involved in a participatory manner among the community to encourage awareness related to the digital economy. After the service was carried out, the community became enthusiastic because it added knowledge about the digital economy by implementing the digital economy in its sales media.